Dampak Buruk Overthinking Bagi Para Remaja - Arrasyid, Raihan Malano; Putra, Muhammad Zidan Wianto (Ikatan Da'i Indonesia, 2024)
This paper discusses the phenomenon of overthinking in students, which is the result of various factors such as anxiety, uncertainty, and social pressure. Overthinking can have a negative impact on a teenager's mental well-being and academic performance. This research explains the causes of overthinking, its negative impacts, and how to overcome overthinking from an Islamic perspective and medical methods. In an Islamic perspective, the concept of tawakal and the principles of positive psychology, such as self-confidence and managing stress, are the basis for overcoming overthinking. Research also highlights the importance of professional support and mental health services in community settings and educational institutions. Medical methods noted included self-talk, being sensitive to oneself, seeking professional help, and turning attention to hobbies. This research emphasizes the need for integration between mental and spiritual health aspects in treating overthinking to achieve effective solutions. It is hoped that through this holistic approach, both from an Islamic and medical perspective, effective solutions can be found to overcome overthinking and improve the quality of life for teenagers, especially students.